Psychological Well-Being at Hospitality: Configuring the Antecedents and Outcomes from Millennials Perspectives - I Gusti Ayu Putu Wita Indrayani; Ni Luh Supartini (Universitas Pendidikan Nasional, 2025)
This study provides a new perspective on the psychological well-being of millennial employees in the Bali hospitality industry by identifying its key predictors and assessing its impact on work and organizational engagement. The study employed explanatory sequential analysis of 153 millennial workers working in various star-rated hotels in Bali. The quantitative analysis with SmartPLS revealed that ambidextrous leadership (beta = 0.578, p < 0.001) and psychological capital (beta = 0.346, p < 0.001) significantly enhanced psychological well-being, while job satisfaction showed a negative effect (beta = -0.186, p < 0.05) and perceived organizational support showed no significant impact (p = 0.160). Furthermore, psychological well-being strongly predicted organizational engagement (beta = 0.760, p < 0.001) and work engagement (beta = 0.705, p < 0.001), with a greater influence on organizational engagement. This study contributes to the literature by demonstrating that psychological well-being exerts a stronger influence on organizational engagement than on work engagement, highlighting millennials’ deeper commitment to their organizations when their well-being is supported. These findings underscore the importance of psychological capital in fostering resilience and offering fresh insights to enhance organizational engagement. Unlike previous research, this study uniquely integrates ambidextrous leadership and psychological capital as primary drivers of psychological well-being, revealing their significant positive influence.